Prenegotiation in South Africa (1985-1993) : a phaseological analysis of the transitional negotiations - Kruger, Botha W. (Botha Willem) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA) -- Stellenbosch University, 1998.